On the evolution of calculation abilities - Ardila, Alfredo (Frontiers in Evolutionary Neuroscience, 2010)
Some numerical knowledge, such as the immediate recognition of small quantities, is observed in animals. The development of arithmetical abilities found in mans evolution as well as in childs development represents a long process following different stages. Arithmetical abilities are relatively recent in human history and are clearly related with counting, i.e., saying aloud a series of number words that correspond to a collection of objects. Counting probably began with finger sequencing, and that may explain the 10-base found in most numerical systems. From a neuropsychological perspective, there is a strong relationship between numerical knowledge and finger recognition, and both are impaired in cases of left posterior parietal damage (angular or Gerstmanns syndrome). Writing numbers appeared earlier in human history than written language. Positional digit value is clearly disclosed in Babylonians, and around 1,000 BC the zero was introduced. Contemporary neuroimaging techniques, specifically fMRI, have demonstrated that the left parietal lobe, particularly the intraparietal sulcus, is systematically activated during a diverse of number tasks; other areas, particularly the frontal lobe, are also involved in processing numerical information and solving arithmetical problems. It can be conjectured that numerical abilities continue evolving due to advances in mathematical knowledge and the introduction of new technologies.